Emotion Coaching in Childhood and Womens’ Romantic Intimacy, Romantic Attachment, and Emotion Regulation in Young Adulthood - Kurta, Jessica (Université d'Ottawa / University of Ottawa, 2016)
The relationship between female undergraduate students’ (n = 151) reports of parental emotion coaching in childhood and their reports of emotion regulation, romantic attachment, and romantic intimacy in young adulthood was investigated. The female undergraduate students completed additional questionnaires about their mood, personality characteristics, and relationship satisfaction in young adulthood, and parental warmth in childhood. Remembered supportive emotion coaching (comprised of Emotion-Focused Reactions, Problem-Focused Reactions and Expressive Encouragement) was significantly and positively correlated with healthier emotion regulation (reappraisal), and was significantly and negatively correlated with less healthy emotion regulation (suppression). Remembered unsupportive emotion coaching (comprised of Minimizing Reactions, Punitive Reactions, and Distress Reactions) was significantly and positively correlated with romantic avoidant and anxious attachment. Romantic intimacy was not significantly correlated with remembered supportive or unsupportive emotion coaching. Emotion regulation mediated the relationship between remembered emotion coaching and avoidant and anxious attachment, but not romantic intimacy. Emotion regulation continued to mediate the relationship between remembered emotion coaching and avoidant attachment after mood, personality characteristics, relationship satisfaction, and parental warmth were entered into the model as covariates, but emotion regulation did not continue to mediate the relationship after covariates were entered into the model when anxious attachment was the predicted variable.
Keywords: emotion coaching; romantic attachment; romantic intimacy; emotion regulation